Multifunctional herbal medicines in small animals in veterinary medicine - Haddad, Felipe Falcão; Pires, Lidia Terêsa de Abreu; Lago, Naiá Carla Marchi de Rezende; Marchi, Patrícia Gelli Feres de; Messias, Cassio Toledo (Seven Editora, 2023)
Rosemary (Rosmarinus officinalis) was used to decline the inflammation levels besides the stress and anxiety that compromise dogs and cats due to the pain and discomfort caused by joint injuries and neurological damage; 3 groups of patients were selected with the assistance of veterinarians and questionnaires that addressed the tutor and animal's profile, besides the pain levels and behavior of the patient during the time of 3 weeks that it's been evaluated. Overall, more than 75% of the patients that received the medicines had a significant improvement with the treatment, having changes like reduction in pain, reduction in lameness, better support in pelvic or thoracic limbs, bigger comfort or reduction in the stress and anxiety levels, proving that the Rosemary can be considered as an effective anti-inflammatory against joint injuries on small animals. DOI:https://doi.org/10.56238/devopinterscie-229